An Analytical Study of the Budget Implementation Process in the Decentralized State Services in Light of the Transition from Line-Item Budgeting to Program and Performance Budgeting in Algeria - zemmit, Fouad (Journal of Research in Finance and Accounting, 2025)
This study seeks to analyze and clarify the process of budget implementation within the decentralized state services in light of the budgetary transition introduced by the Organic Law on Finance Laws (LOLF). Through this reform, Algeria has shifted from a traditional line-item budgeting system—based on inputs and financial means—to a program and performance budgeting approach that emphasizes future programs, measurable outcomes, and achieved results. The findings indicate that the previously adopted line-item budgeting framework no longer meets the requirements of modern public resource management, particularly in the context of digital transformation. This system relies on conventional procedures that fail to ensure the efficient and transparent management of state resources and capacities. Consequently, Algeria has adopted program and performance budgeting as a strategic alternative, marking the first step toward the modernization of its budgetary and accounting framework. Furthermore, the study concludes that the effective implementation of this new budgeting model and the attainment of its intended objectives require a thorough understanding of the reforms introduced under the LOLF and their practical implications for decentralized financial governance.